Effect of Product Diversity, Price and Location on Consumer Satisfaction - Hasrudding Hasrudding (Newinera Publisher, 2022)
The primary objective of this study is to ascertain the inherent importance of various factors in influencing consumer satisfaction, with the ultimate goal of identifying the most influential factor among them. The data collection process encompassed a comprehensive array of methodologies, including meticulous observation, extensive literature review, thought-provoking questionnaires, meticulous documentation analysis, and insightful interviews. A comprehensive study was conducted, encompassing a sample size of 40 individuals who were selected through the implementation of accidental sampling methodology. The data underwent rigorous analysis employing quantitative methodologies, encompassing assessments of validity and reliability, alongside the application of multiple linear regression analysis. The findings of the study reveal that various factors, namely product diversity, price, and location, exert a noteworthy influence on consumer satisfaction when examined in isolation. The statistical analysis, specifically the t-test, revealed that the coefficients pertaining to all three factors exhibited a noteworthy level of significance (p < 0.05). Moreover, the statistical analysis conducted through the F-test has demonstrated that the combined influence of the three factors under investigation exerts a noteworthy impact on consumer satisfaction, as indicated by the obtained p-value of less than 0.05. The results of the determination test have revealed that the combined influence of the variables under consideration accounts for a substantial portion, specifically 74.2%, of the observed variability in consumer satisfaction.